2009
DOI: 10.1016/j.nima.2009.07.085
|View full text |Cite
|
Sign up to set email alerts
|

Ultra cold neutron production by multiphonon processes in superfluid helium under pressure

Abstract: Cold neutrons are converted to ultra-cold neutrons (UCN) by the excitation of a single phonon or multiphonons in superfluid helium. The dynamic scattering function S(q, ω) of the superfluid helium strongly depends on pressure, leading to a pressuredependent differential UCN production rate. A phenomenological expression for the multiphonon part of the scattering function s(λ) describing UCN production has been derived from inelastic neutron scattering data. When combined with the production rate from single ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
(39 reference statements)
1
34
0
Order By: Relevance
“…The single-phonon UCN production peak moves to a shorter wavelength and decreases in intensity, whereas the absolute contribution from multiphonon processes stays constant within the experimental uncertainties. We have found that predictions from calculations based on inelastic neutron scattering data [32,33] agree well with the behavior of the single-phonon UCN production rate. However, the same calculations disagree with our measurement in the multiphonon range.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The single-phonon UCN production peak moves to a shorter wavelength and decreases in intensity, whereas the absolute contribution from multiphonon processes stays constant within the experimental uncertainties. We have found that predictions from calculations based on inelastic neutron scattering data [32,33] agree well with the behavior of the single-phonon UCN production rate. However, the same calculations disagree with our measurement in the multiphonon range.…”
Section: Discussionmentioning
confidence: 60%
“…This behavior can be well understood by taking a , and UCN production rates compared with results given in Refs. [32,33] calculated from scattering data. UCN production rates are normalized to the incident cold neutron flux.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations